Advances in the study of ELABELA in renal physiological functions and related diseases - Liu, YuRong; Jiang, MingChun; Li, Yue; Chen, Peng; Chen, XiaoYu (Frontiers in Pharmacology, 2023)
ELABELA (ELA), also known as Toddler or Apela, is a novel endogenous ligand of the angiotensin receptor AT1-related receptor protein (APJ). ELA is highly expressed in human embryonic, cardiac, and renal tissues and involves various biological functions, such as embryonic development, blood circulation regulation, and maintaining body fluid homeostasis. ELA is also closely related to the occurrence and development of acute kidney injury, hypertensive kidney damage, diabetic nephropathy, renal tumors, and other diseases. Understanding the physiological role of ELA and its mechanism of action in kidney-related diseases would provide new targets and directions for the clinical treatment of kidney diseases.